Sambiloto (Andrographis paniculata Nees.) for reducing aflatoxsins contamination in commercial chicken feed - Sri Rachmawati; zainal Arifin; Paderi Zahari (Jurnal Ilmu Ternak dan Veteriner, 1999)
Indonesian climate condition is suitable for growing of mold such as Aspergillus flavus. The mold grown in feed and feed ingredients cause aflatoxins contamination of the feed. Sambiloto has been reported to reduce the growth of Aspergillus flavus and aflatoxins production in feed isolate. The aim of the study was to find the used of sambiloto in reducing aflatoxins contamination in commercial chicken feed. The feed was homogenously mixed then divided into 4 groups with 3 replicates. The samples were treated with sambiloto 0.04%, 0.08% and 0.16% respectively into the feed, except for the control feed sambiloto was not added. Into these feed 4 ml of Aspergillus flavus suspension was also added. Then the feed in each group was incubated at room temperature for 10 days. Samples were collected from each group at days 0, 5 and 10 of incubation times for aflatoxins analysis. Samples were extracted and aflatoxins were detected by High Performance Liquid Chromatography (HPLC). Observation results indicated that sambiloto concentration of 0.16% in feed can inhibit the total aflatoxins production of 16.46% and gave the inhibitation percentage of aflatoxin B1 of 45.39%. Statistical test showed that the used of sambiloto in feed for 5 days incubation times gave significant result in reducing aflatoxins production. However the 10 days incubation times of the feed with sambiloto gave in significant result. It is suggested that to get optimum inhibition of aflatoxins production, sambiloto added in feed should be higher than 0.16%.   Key words : Feed, aflatoxin, sambiloto